The Syntactic Structure of Polish Pleonasms - Ruszkowski, Marek (Respectus Philologicus, 2006)
A pleonasm is a redundant combination in which elements are in a superior-subordinate relation, and the subordinate element reiterates the meaning of the superior element. The elements may be ordered in two ways: 1. superior element - subordinate element; 2. subordinate element - superior element. However, it does not affect the syntactic structure of the analysed combinations. The syntactic structure is determined by the function of the subordinate part in the sentence, whether it is an attribute, adverbial or object (or a component difficult to identify in syntactic terms). Thus, there are four classes of pleonastic structures. The material collected comprising 307 pleonasms also allows us to single out some subclasses - 3 within combinations with an attribute and 8 within combinations with an adverbial, which makes 13 groups, including pleonasms with objects and difficult-to-classify structures. Despite this diversity, a dominant role is played by one type - structures with an adjectival attribute - which accounts for nearly 54% of all collected combinations. The frequency of other types is below 50%, and the most frequent among them are pleonasms with a nominal attribute (more than 11 % of all combinations), with an adverbial of manner (almost 9%), with a prepositional attribute (more than 6%). The least frequent are structures with an adverbial of purpose (0,3%) and with an adverbial of stage and respect (0,7% each). Many analysed pleonasms justified a supposition that the observed regularities apply to all pleonastic structures in contemporary Polish.